Pemanfaatan Tenaga Surya Pada Photovoltaic Jenis Polycristaline Untuk Catu Daya Tanaman Hidroponik - Samsurizal Samsurizal; Max Teja Aji; Kartika Tresya M (Energi & Kelistrikan, 2021)
The use of solar energy today as an alternative energy source continues to be used not only in large scale but also utilized on small scale. The use of solar power as a renewable energy source by converting solar energy into electrical energy, utilizing this technology one of them on technology using hydroponic plant systems. In hydroponic pump system used to consume water and nutrients are usually sourced electricity PLN. With the availability of abundant energy sources certainly help reduce electricity consumption from PLN. The design is done on this research by utilizing solar energy as a power supply to turn on the pumps as well as to drain water and plant nutrients running well. The burden used in this study was 20Watt, to supply the load needs of a PLTS fitted with polycristaline type. The highest irradiation at 12.00 is 666 W/M2 which means that at that time the energy is generated maximally. In the design used with the battery capacity using the VRLA Deep Cycle JS12-12 battery type; 12V 12Ah generated and stored electrical energy can turn the 5-6 hour pump on.